Design and development of groceries ordering system with QR code / Mahfudzah Othman ... [et al.] - Othman, Mahfudzah; Mohamad Sakri, Illi Najwa; Muhd Zain, Nurzaid; Paidi, Zulfikri; Che Jan, Nora Yanti; Kamarudin, Nur Khairani (UiTM Cawangan Perlis, 2021)
E-commerce is one of the innovations that has started to become a new norm in this millennium. Due to the time-consuming physical shopping activities, the increase in living expenses, and the increase of responsibilities, people tend to find new ways to adapt to this new norm. Thus, buying groceries online has also been the preferred way for many people nowadays as it could save time and reduce daily hassles. This paper discusses the design and development of a web-based Groceries Ordering System with QR Code that was built using the web-based applications such as PHP, HTML and MySQL. The design and development of the prototype system involves three main phases, which are the system design, system development and system testing and took into consideration five criteria of the end-user satisfaction of an online shopping system, which are the system's content, accuracy of information, format of the information displayed, ease of use and timeliness. The prototype system will also incorporate the QR code technology where it provides functions for information of products' purchases and transactions. Upon completion of the prototype system, testing for usability among potential end-users was conducted, where it focusses on system's usefulness, information quality and interface quality. Forty participants have completed the usability testing, and the results have showed that the Groceries Ordering System with QR Code has fulfilled all the five criteria of end user's satisfaction.